A multidimensional study of male transvestite homosexuals and male homosexuals - Stanley Rabinowitz (Department of Psychology, 2024)
A sample of 12 males, 7 transvestites and 5 homosexuals, obtained mainly from a non-psychiatric population underwent a variety of tests in order to investigate: (1) Early developmental patterns (through the use of an unstructured clinical interview, an Interview Schedule of Money and Primrose 1969 and a questionnaire of early childhood relationships of Evans 1969); (2) The phenomenon of alienation (through the use of Rotter's I-E scale 1966 and Nettler's Alienation Scale 1957); (3) The amount of heterosexual activity (through the use of Bentler's Heterosexual Behaviour Assessment Questionnaire 1968); and (4) Personality dynamics (through the use of the Rorschach, MMPI and CPI). Mention should be made that early developmental patterns were studied only with the transvestite sample. A multi-dimensional approach was used which aimed at obtaining a comprehensive, overall picture of personality. No significant differences were obtained between .the groups on the tests measuring alienation and heterosexual activity. However on all the tests of personality the transvestite sample clearly showed themselves to be more psychologically and socially disturbed than did the homosexuals. The grossly retarded personalities of the transvestites was assumed to have been a result of their grossly disturbed early developmental patterns especially their pathologically dependent relationship with their mothers. A schizophrenic process was clearly evident in the transvestite sample, but was markedly absent from the homosexual sample.